DETERMINANTS OF ACCOUNTING STUDENTS’ INTENTION TO TAKE PROFESSIONAL ACCOUNTANT CERTIFICATION - Niswatin, Khoirun; Rochayatun, Sulis (UNKLAB Business School, 2024)
This study aims to examine and analyze the influence of the level of understanding, attitude, career motivation, degree motivation, and financial rewards on students' intention to pursue professional accountant certification. The research adopts a quantitative descriptive methodology, focusing on fifth and seventh-semester accounting students at UIN Maulana Malik Ibrahim Malang. Through purposive sampling, 73 individuals were selected as the study sample. Multiple linear regression analysis using SPSS version 25 was employed as the analytical method. The results indicate that students' intention to pursue professional accountant certification is positively and significantly influenced by their attitude and financial rewards. However, the intention is not affected by the level of understanding, degree motivation, or career motivation. Keywords: Level of understanding, attitude, motivation, financial reward, professional accountant certification Penelitian ini bertujuan untuk mengevaluasi dan mengurai pengaruh tingkat pemahaman, sikap, motivasi karir, motivasi gelar, dan penghargaan finansial terhadap niat mahasiswa untuk memperoleh sertifikasi sebagai akuntan profesional. Penelitian ini menggunakan pendekatan deskriptif kuantitatif, dengan populasi yang terdiri dari mahasiswa akuntansi semester lima dan tujuh di UIN Maulana Malik Ibrahim Malang. Dengan menggunakan purposive sampling, sebanyak 73 orang menjadi sampel penelitian. Analisis regresi linier berganda dengan menggunakan SPSS versi 25 digunakan sebagai metode analisis. Hasil penelitian menunjukkan bahwa sikap dan penghargaan finansial memiliki pengaruh positif dan signifikan terhadap niat mahasiswa untuk mendapatkan sertifikasi akuntan profesional. Namun, tingkat pemahaman, motivasi gelar, dan motivasi karir tidak mempengaruhi niat mahasiswa untuk mengikuti sertifikasi akuntan profesional. Kata kunci: Tingkat pemahaman, sikap, motivasi, penghargaan finansial, sertifikasi akutan profesional